Bhumi Sangtu Ubud Bali: A Sustainable Guest House Development Globally Oriented Locally Contextualized - Wiryani, Ni Nyoman Sri; Ernawati, Ni Made; Oka, I Made Darma; Arjana, I Wayan Basi (International Journal of Science and Society, 2025)
This article presents a sustainable boutique hotel development located in Ubud, Bali, Indonesia. This boutique hotel marketed as Bhumi Sangtu Resort Ubud was built in 2023-2024. Given the many accommodations available and have mushroomed recently in Kedewatan village, Ubud, it is very important for this property to have its own value and uniqueness; implementing sustainable tourism values and principles is opted as a competitive advantage which is applied from the construction stage up to its operation. ​​ Data collection techniques used in this research included observation, documentation studies, and focus group discussions. The development of Bhumi Sangtu Resort Ubud used POAC management of planning, organizing, actuating and controlling, each stage of development integrating the concepts of sustainable tourism including three pillars of sustainability: economic, social-cultural, as well as environment. Pertinent to the guest house development, the controlling stage was carried out by monitoring the project throughout the development process, until few months after the guest house is launched.